THE METHOD OF WORKING WITH THE CHOIR TEAM - Musurmonkulov Husniddin Nuriddinovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
In 1960, in order to preserve nationalism in professional choral performance, a choral group was established under the umbrella of the Uzbek Television and Radio. The famous conductor, talented composer, connoisseur of choral music, People's Artist of Uzbekistan Botir Umidjonov was appointed as its leader. He was not only the leader, but also the program creator of the team. it can be said with confidence that professional choral performance was fully formed in Uzbekistan in the 70s of the 20th century. During this short period, a new art form and its performance were mastered by national artists and performers.